Plant virus diversity in bee and pollen samples from apple (Malus domestica) and sweet cherry (Prunus avium) agroecosystems - Smadi, Malek; Lee, Eunseo; Phelan, James; Wang, Aiming; Bilodeau, Guillaume J.; Pernal, Stephen F.; Guarna, M. Marta; Rott, Mike; Griffiths, Jonathan S. (Frontiers in Plant Science, 2024)
Honey bee (Apis mellifera) pollination is widely used in tree fruit production systems to improve fruit set and yield. Many plant viruses can be associated with pollen or transmitted through pollination, and can therefore be detected through combining metagenomics and bee pollination activities. Honey bees visit multiple flowers and individuals in one foraging trip, essentially sampling small amounts of pollen from a wide area. Here we report metagenomics-based area-wide monitoring of plant viruses in cherry (Prunus avium) and apple (Malus domestica) orchards in Creston Valley, British Columbia, Canada, through bee-mediated pollen sampling. A wide array of viruses were identified in both cherry and apple systems, with cherry virus A (CVA), prune dwarf virus (PDV), prunus necrotic ringspot virus (PNRSV), and prunus virus F (PVF) being particularly widespread. Citrus concave gum associated virus, and apple stem grooving virus, apple mosaic virus, and apple hammerhead viroid were only identified in samples collected during apple bloom, demonstrating detection of viruses collected from the same site at different times specific to each tree species. Different profiles of viruses were identified in bee and pollen samples compared to leaf and flower samples reflective of pollen transmission affinity of individual viruses, or contamination from unknown hosts. Phylogenetic and pairwise analysis of the coat protein regions of the four major viruses (CVA, PDV, PNRSV, and PVF) identified showed unique patterns of nucleotide sequence diversity, which could have implications in their evolution and management approaches. Coat protein sequences of CVA and PVF were broadly diverse with multiple distinct phylogroups identified, while PNRSV and PDV were more conserved. Multiple variants of all four viruses were identified in samples collected during apple and cherry bloom, suggesting a complex system rich in viral diversity, with complex and partially overlapping potential host ranges. This research helps to further define the pollen virome in fruit production systems, and provide further examples of the benefits of area-wide monitoring approaches.